2016
DOI: 10.18235/0000310
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Violence, and Drugs Among Latin American and Caribbean Adolescents: Do Engaged Parents Make a Difference?

Abstract: work is licensed under a Creative Commons IGO 3.0 AttributionNonCommercial-NoDerivatives (CC-IGO BY-NC-ND 3.0 IGO) license (http://creativecommons.org/licenses/by-nc-nd/3.0/igo/ legalcode) and may be reproduced with attribution to the IDB and for any non-commercial purpose, as provided below. No derivative work is allowed.Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The 3 items measuring parental involvement were averaged to form a parental involvement composite variable and the internal consistency of the parental involvement construct was .64. A prior research study using GSHS data (Ruprah et al, 2017) has demonstrated reliability and validity of the 3-item measure of parental involvement used in the current investigation. Ruprah, Sierra, and Sutton (2017) found that higher scores on parental involvement were associated with lower levels of risk behavior.…”
Section: Methodsmentioning
confidence: 75%
See 2 more Smart Citations
“…The 3 items measuring parental involvement were averaged to form a parental involvement composite variable and the internal consistency of the parental involvement construct was .64. A prior research study using GSHS data (Ruprah et al, 2017) has demonstrated reliability and validity of the 3-item measure of parental involvement used in the current investigation. Ruprah, Sierra, and Sutton (2017) found that higher scores on parental involvement were associated with lower levels of risk behavior.…”
Section: Methodsmentioning
confidence: 75%
“…Alcohol use —“During the past 30 days, on how many days did you have at least one drink containing alcohol?” Response options were 1 = 0 days , 2 = 1 or 2 days , 3 = 3–5 days , 4 = 6–9 days , 5 = 10–19 days , 6 = 20–29 days , and 7 = all 30 days . Several existing studies using GSHS data support the validity of the single-item measures of tobacco and alcohol use (Banzer et al, 2017; Mazaba et al, 2017; Mouhanna et al, 2017; Murshid, 2017; Peltzer & Pengpid, 2017a, 2017b; Ruprah et al, 2017; Ziaei et al, 2017). For example, Banzer et al (2017) found significant positive associations between adolescents’ tobacco use and anxiety, hyperactivity, conduct problems, self-injurious behaviors, previous suicide attempts, alcohol and drug use, and family problems.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Engaged parents were associated with significantly reduced problem behaviours among adolescents in the Caribbean and Latin America (Ruprah, Sierra, and Sutton 2016). While the Caribbean had fewer engaged parents than Latin America, and the impact of good parenting was weaker in the Caribbean, engaged parenting made a significant difference for both groups of countries (Appendix 5.1).…”
Section: Early Problem Behaviours Risk and Protective Factorsmentioning
confidence: 99%
“…A recent IDB study using data from the GSHS investigated the prevalence of five problem behaviours among adolescents ages 13-17-sexual intercourse, drinking, drug use, fighting, and getting in trouble after drinking-in Latin America and the Caribbean (Ruprah, Sierra, and Sutton 2016). Figure 5.4 shows that levels of problem behaviours were generally higher in the Caribbean countries than in the Latin American countries surveyed.…”
Section: Early Problem Behaviours Risk and Protective Factorsmentioning
confidence: 99%